Step-by-step explanation:
Given
f(x) = 8x - 9
Then
For a.
f(3y - 1 ) = 8(3y - 1 ) - 9
= 24y - 8 - 9
= 24y - 17
Now for b.
f(x) = - 23
or, 8x - 9 = - 23
8x = - 23 + 9
8x = - 14
x = - 14 / 8
x = - 7 / 4
Hope it will help :)
Answer:
add 1 and subtract 1
Step-by-step explanation:
so if u add and subtract 1. take 5. 5+1 and -1 is 4 and 6
Hope this helps :D
solve for x.
4x−5=7+4y
Add 5 to both sides.
4x−5+5=4y+7+5
4x=4y+12
Divide both sides by 4.
4x/4=4y+12/4
x=y+3
-----------------------------------------------------
Have a nice day! :)
3b because b^2-4= 1/b. So 2/1/b= 2b b+2b = 3b